Limnologia comparativa de três lagoas neotropicais da Bacia do Magdalena Médio Santandereano (Colômbia), com ênfase no estudo da diversidade da comunidadezooplanctônica e sua relação com a dinâmica hidrológica do sistema regional - Gavilán-Diaz, Rosa Aura (2000)
Few studies have been developed regarding zooplankton diversity in Neotropical Region, particularly in Colombia. Regarding the diversity in the Tropical region still there are a great controversy, despite the relevance of this community as indicator of climate or hydrological, physical and chemical changes. A limnological study was performed during the period between January, 1998 and January 1999, in three shallow lakes ( ciénagas ) belonging to Rio Magdalena Basin, Middle Santandereano,-Colômbia. At monthly intervals a set of physical, chemical and biological variables were measured in a sampling station at the central region of the lakes. The effects of rainfall and water level on Shannon-Wiener zooplankton diversity index were analyzed. Also analyses of taxonomical composition and relative abundance of zooplankton community as a whole or for the Rotifera, Cladocera and Copepoda were performed showing differences among the lakes. A similar thermal structure with microstratification in surface layers and gradual decreases with depth was observed. Maximum temperature value found was 38º C in the surface and 26.8ºC at the bottom. Physical and chemical conditions varied along the hydrological cycle, although there was not a defined pattern except regarding nutrient concentrations that was observed to be higher in the lowest water level and suffering dilution in the wet period for all lakes. The highest values of Chlorophyll a (229.2 µg.L-1) and net primary production (3203 mg C m2d-1) were found in Ciénaga of Chucuri Lake. It appears that there is an inverse relationship between total zooplankton densities and chlorophyll a concentrations. The highest richness of taxa was observed in Ciénaga El Llanito. Rotifers had the highest annual numerical relative abundance and also the highest taxonomical richness in all lakes, throughout the hydrological cycle. There appears to be an alternation in the dominance of species for each particular group of zooplankton in the three ciénagas However it does not appear to be a succession pattern. The highest Shannon-Wiener índices were obtained for Ciénaga de Paredes (4.12 bits.ind-1) and the smallest for Ciénaga de Chucurí (1.24 bits.ind-1) and simultaneously a higher equitability was found, suggesting that the highest diversity indices were related to uniformity. There was no correlation found among water level fluctuation and zooplankton density as a whole, but this exists when the component groups were considered alone, as it was found for Cladocera in Ciénaga de Paredes. The absence of correlation among zooplankton diversity indices and water level fluctuations suggest that each group probably responds to multiple interacting factors in each lake.